Evaluasi Kinerja Ruas Jalan Raya Panjang Jiwo Permai Akibat Pembangunan Rumah Sakit Ubaya Kota Surabaya - Hanum Cahyani, Salfa; Hadi Putra, Kurnia (Jurnal Etnik: Ekonomi-Teknik, 2023)
The traffic on Jalan Panjang Jiwo Permai before the construction of the hospital was quite heavy due to obstacles from cars leading to the Ubaya University parking lot, these obstacles will continue to increase because the road is a commercial area. In the commercial area of the road there are many shop houses and schools around the road which create big obstacles during school or work hours and when going home. The construction of the Ubaya Hospital has added to the traffic obstacles on the road because many trucks of construction materials will frequently cross the road. So it is necessary to carry out an analysis of the performance evaluation of the road sections due to the development to determine the speed value for the comfort of road users. This study uses the 1997 MKJI method as the basis for the analysis of road evaluation calculations. In this analysis, the researcher obtains the components of the calculation by conducting field surveys directly on weekdays and holidays. The results obtained from this study were that before the construction of road users used a speed of 48 km/hour, then during construction there was a decrease in speed of 43 km/hour by road users which caused inconvenience to road users and reduced the quality of workers' time due to traffic barriers.